Pathways for Indigenous Education in the Australian Curriculum Framework - Nakata, Martin (The Australian Journal of Indigenous Education, 2011)
This article reflects on pathways for Indigenous education in the developing agenda of the Australian Curriculum, the cross-curriculum priorities, the general capability area of intercultural understanding, and the positioning of Indigenous learners within the diversity of learners with English as an additional language or dialect (EALD).